(untitled) (Research, Society and Development, 2021)
The Brazilian agricultural production exceeds the storage capacity, with that the construction of a silo becomes essential. he physical and flow characteristics of the analyzed product is essential in silo design. Therefore, this work aims to determine the physical and flow properties of different common bean cultivars for dimensioning vertical silos. The experiment was conducted at the Laboratory of Rural Constructions and Ambience - LACRA of the Federal University of Campina Grande, in the city of Campina Grande-PB, analyzing the different types of beans: carioquinha (Phaseolus vulgaris L.), black (Phaseolus vulgaris L.) and macassar (Vigna unguiculata). The physical characteristics (moisture content, granulometry, density) and flow (angle and effective internal friction angle, average cohesion and friction angle existing between the product and different silo wall materials) were measured. wall: acrylic, smooth steel, rough steel, aluminum, wood, analyzing the best option. It was concluded that the products are classified as coarse grains, with free flow, for hopper inclination there was a numerical difference between the analyzed walls.